2022
DOI: 10.3390/molecules27010271
|View full text |Cite
|
Sign up to set email alerts
|

Propolis and Diet Rich in Polyphenols as Cariostatic Agents Reducing Accumulation of Dental Plaque

Abstract: Conducted studies indicate the relationship between oral health and systemic diseases. Moreover, the latest research indicated that cariogenic bacteria may severely influence the course of SARS-CoV-2 infection and increase risk of COVID-19 complications. This article aims to review various applications of propolis and pay attention to a healthy diet rich in polyphenols, which may allow the reduction of dental plaque accumulation. A literature review has been conducted from June until November 2021. It showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…These compounds also play essential roles in antioxidant, antibacterial, immunomodulatory, and wound‐healing activities (Oryan et al, 2018). Based on the literature, polyphenolic compounds of propolis possess cariogenic properties and reduce the accumulation of dental plaques and improve oral health (Kurek‐Gorecka et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds also play essential roles in antioxidant, antibacterial, immunomodulatory, and wound‐healing activities (Oryan et al, 2018). Based on the literature, polyphenolic compounds of propolis possess cariogenic properties and reduce the accumulation of dental plaques and improve oral health (Kurek‐Gorecka et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature, polyphenolic compounds of propolis possess cariogenic properties and reduce the accumulation of dental plaques and improve oral health (Kurek-Gorecka et al, 2022).…”
Section: Tpc Tfc and Antioxidant Potencymentioning
confidence: 99%
“…In chronic periodontitis, compared to healthy gingiva, the concentrations of pro-inflammatory cytokines, such as IL-1β, IL-6, TNF-α, and inflammatory mediators, like prostaglandins and metalloproteinases, increase significantly. This can result in the destabilization of the atherosclerotic plaque, which is a major cause of acute coronary syndromes and myocardial infarction [ 3 ]. In vitro and in vivo studies have shown that natural compounds, including propolis, possess anti-inflammatory [ 22 ], antioxidant [ 23 ], anticancer [ 24 ], neuroprotective [ 25 ], antiviral [ 26 ], antibacterial [ 27 ], or immunomodulatory properties [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is caused by bacterial infection of the gums, periodontium, adjacent alveolar bone, and root cement. Among the bacteria which are responsible for inflammation in periodontal tissue are Porphyromonas gingivalis , Treponema denticola , Tannarella forsythia , Bacteroides forsythus , Aggregatibacter actinomycetemcommitans , Prevotella intermedia , Streptococcus sanguis , and Fusobacterium nucleatum [ 2 , 3 ]. Bacteria and their products present in the biofilm stimulate immunocompetent cells to produce and release inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Gingivitis and periodontitis may last for months or years and spread slowly the body when the bacteria enter the blood stream, leading to the release of a variety of inflammatory mediators [ 56 , 57 ]. Dental plaque, a unique biofilm, contains a wide variety of bacteria, viruses, and fungi [ 58 ]. Oral bacteria can be sub-classified according to their oxygen requirements.…”
Section: Orodental Healthmentioning
confidence: 99%